Anxiety Barriers in Joining Digital Online Learning During Covid19 Pandemic Outbreaks - Cahyadi, Ani (el Buhuth: Borneo Journal of Islamic Studies, 2021)
Pandemic covid19 outbreaks brings many impacts in education sectors including to conduct and maintain teaching and learning at university. This study evaluates the use of digital online learning hosted by Islamic university in Indonesia. Students’ anxiety in joining and following the distance classroom is the major factor that was analyzed. quantitative approach was used to get and investigated the data beyond the sample students of university. Throwing the students’ perception in the online survey which was conducted to portray the data on the why students felt anxiety to get the digital online learning. Research findings explain about the students owning technological items in supporting students’ online learning and students’ anxiety while attending and joining the online classroom. The discussion discloses about 1) the readiness of students’ having online devices, internet settings, and students’ literacy in using online technology. 2) Moreover, it also elaborates students’ anxiety claiming that digital online learning scared and make them less confidence, bad feeling, and lack of enthusiastic to study. the writer concludes that students presume these followings; -prefer having online classroom using smartphones android rather than laptop/computer pc, -got trouble in internet connection while having online classroom, - sacrifice much money to consume internet quota to join online learning, - scared students due to the equipment needed, - do not feel confidence in joining the lesson due to many obstacles and barriers.